Comportamento da adição do carbeto de nióbio (nBC) na matriz metálica do aço ferrítico 15kH2mfa - Silva Júnior, José Ferreira da (2012)
The 15Kh2MFA steel is a kind of Cr-Mo-V family steels and can be used in turbines for energy generation, pressure vessels, nuclear reactors or applications where the range of temperature that the material works is between 250 to 450°C. To improve the properties of these steels increasing the service temperature and the thermal stability is add a second particle phase. These particles can be oxides, carbides, nitrites or even solid solution of some chemical elements. On this way, this work aim to study the effect of addition of 3wt% of niobium carbide in the metallic matrix of 15Kh2MFA steel. Powder metallurgy was the route employed to produce this metallic matrix composite. Two different milling conditions were performed. Condition 1: milling of pure 15Kh2MFA steel and condition 2: milling of 15Kh2MFA steel with addition of niobium carbide. A high energy milling was carried out during 5 hours. Then, these two powders were sintered in a vacuum furnace (10-4torr) at 1150 and 1250°C during 60 minutes. After sintering the samples were normalized at 950°C per 3 minutes followed by air cooling to obtain a desired microstructure. Results show that the addition of niobium carbide helps to mill faster the particles during the milling when compared with that steel without carbide. At the sintering, the niobium carbide helps to sinter increasing the density of the samples reaching a maximum density of 7.86g/cm³, better than the melted steel as received that was 7,81g/cm³. In spite this good densification, after normalizing, the niobium carbide don t contributed to increase the microhardness. The best microhardness obtained to the steel with niobium carbide was 156HV and to pure 15Kh2MFA steel was 212HV. It happened due when the niobium carbide is added to the steel a pearlitic structure was formed, and the steel without niobium carbide submitted to the same conditions reached a bainitic structure